2012
DOI: 10.1002/pmic.201100586
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic profiling of high glucose primed monocytes identifies cyclophilin A as a potential secretory marker of inflammation in type 2 diabetes

Abstract: Hyperglycemia is widely recognized to be a potent stimulator of monocyte activity, which is a crucial event in the pathogenesis of atherosclerosis. We analyzed the monocyte proteome for potential markers that would enhance the ability to screen for early inflammatory status in Type 2 diabetes mellitus (T2DM), using proteomic technologies. Monocytic cells (THP-1) were primed with high glucose (HG), their protein profiles were analyzed using 2DE and the downregulated differentially expressed spots were identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 57 publications
2
31
0
1
Order By: Relevance
“…CyPA, an important inflammatory mediator in development of AS, is a potent chemoattractant for leukocytes, monocytes, and lymphocytes; within the plaques, macrophages can secrete large amounts of CyPA when stimulated by ROS [24][25][26]. Studies have shown highly expressed CyPA in advanced atherosclerotic lesions.…”
Section: Discussionmentioning
confidence: 99%
“…CyPA, an important inflammatory mediator in development of AS, is a potent chemoattractant for leukocytes, monocytes, and lymphocytes; within the plaques, macrophages can secrete large amounts of CyPA when stimulated by ROS [24][25][26]. Studies have shown highly expressed CyPA in advanced atherosclerotic lesions.…”
Section: Discussionmentioning
confidence: 99%
“…CyPA has been found to be secreted into the extracellular space by several types of cells, such as foam cells (14), vascular smooth muscle cells (15), and macrophages (16). In patients, higher levels of soluble extracellular CyPA can be detected under inflammatory conditions, for example, in nasal fluids of patients with asthma (35), in plasma of patients with type 2 diabetes (16), and in serum of patients with coronary artery disease (36). The exact mechanism by which CyPA is secreted from the intracellular to extracellular space has not been well described.…”
Section: Discussionmentioning
confidence: 99%
“…The most abundant of these is cyclophilin A (CyPA), which makes up 0.1-0.6% of all cytosolic proteins (13). Although CyPA is present intracellularly, it can be secreted from cells in response to inflammatory stimuli, such as hypoxia, infection, and oxidative stress (14)(15)(16). cluster of differentiation 147 (CD147), a type I transmembrane protein, was found to be the cell surface signaling receptor for extracellular CyPA.…”
Section: E369mentioning
confidence: 98%
“…The relationship between metabolic problems, such as obesity, diabetes and elevated lipids, and the expression of Apo has been frequently investigated in the general population (Padrao, Ferreira, Vitorino, & Amado, 2012;Ramachandran et al, 2012;Sadler et al, 2012). Due to antipsychotic medications in SZ and mood stabilisers in BD, those patients have an increased risk for metabolic disturbances and altered lipid metabolism (Gibbons, Thomas, Scarr, & Dean, 2010), ultimately contributing to an increased risk for cardiovascular disease (Meyer et al, 2008).…”
Section: Strength and Limitationsmentioning
confidence: 99%